The Relationship between the Implementation of Field Work Practices and the Work Readiness of Class XI Students of Audio Vidio Engineering 2 SMK Negeri 4 Medan to the World of Work - Sukarman Purba; Samuel Munte; Rismauli Napitupulu; Adong Rumahorbo (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the relationship between the implementation of Field Work Practices (PKL) and the work readiness of students of SMK Negeri 4 Medan Class XI Audio Vidio 2 Engineering in the world of work. The sample in this study were Class XI Audio Vidio 2 students consisting of 21 students. Data collection is done by using a questionnaire. From the results obtained it was concluded that Field Work Practice (PKL) has a positive relationship to the work readiness of students of SMK Negeri 4 Medan Class XI Audio Vidio 2 Engineering in facing the world of work in the future. This can be concluded from the percentage results obtained, namely, 87.4% which is a very high percentage value. Based on the data obtained, the level of readiness in facing the world of work of students has a very high level of readiness, this is obtained from the percentage results which get a percentage value of 81.4%.